MENGEMBANGKAN USAHA MELALUI WEBSITE DAN DIGITAL MARKETING PADA USAHA TERALIS DI KOTA BATAM - Saut Pintubipar Saragih; Mesri Silalahi; Afriana Afriana (PUAN INDONESIA, 2022)
Content management system (CMS) is something that is no longer new for all web developers (developers) because currently the platforms used by developers are almost entirely using the concept of a content management system. In this community service activity, coaching has been carried out for business actors in the Barlang Jaya Trellis trellis welding workshop or workshop to have the ability to create a media product and service that you want to market, promote and sell to potential consumers through Content management system software, namely wordpress. During the training phases, instructor deliver basics knowledge in managing websites content and processes to build it, the training includes manage the web admin section, control panel settings also distributed through training to the owners which the results expect the continuity of the development in the future. The marketing, promotion and sales media that are built based on this website are expected to be affected and boost the business possible to increase competitiveness and increase income and increase business processes efficiency in promotion or marketize the products or services and eventually increasing sales significantly.